2017
DOI: 10.1021/acs.joc.7b01069
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Mechanism of Intramolecular Cu-Directed Hydroxylation of sp3 C–H Bonds

Abstract: The use of copper in directed C−H oxidation has been relatively underexplored. In a seminal example, Schönecker showed that copper and O2 promoted the hydroxylation of steroid-containing ligands. Recently, Baran (J. Am. Chem. Soc. 2015, 137, 13776) improved the reaction conditions to oxidize similar substrates with excellent yields. In both reports, the involvement of Cu2O2 intermediates was suggested. In this collaborative article, we studied the hydroxylation mechanism in great detail, resulting in the overh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 68 publications
6
89
0
1
Order By: Relevance
“…The primary differences result from the timing of the delivery of protons and electrons to the Cu/O 2 complex. However, H 2 O 2 has been shown to react with biomimetic Cu(I) complexes to oxidize substrates through Fenton-like chemistry, where homolytic cleavage of the O-O bond generates powerful and nonselective hydroxyl radicals (31)(32)(33). Evidence has pointed to O 2 as the cosubstrate for the mononuclear Cu center in PMOs (16,17), but a recent report concluded that H 2 O 2 is the cosubstrate (7).…”
Section: Discussionmentioning
confidence: 99%
“…The primary differences result from the timing of the delivery of protons and electrons to the Cu/O 2 complex. However, H 2 O 2 has been shown to react with biomimetic Cu(I) complexes to oxidize substrates through Fenton-like chemistry, where homolytic cleavage of the O-O bond generates powerful and nonselective hydroxyl radicals (31)(32)(33). Evidence has pointed to O 2 as the cosubstrate for the mononuclear Cu center in PMOs (16,17), but a recent report concluded that H 2 O 2 is the cosubstrate (7).…”
Section: Discussionmentioning
confidence: 99%
“…26 Examples of [CuOOR] + complexes reacting with C H bonds are numerous, with reports of hydroxylations of strong sp 3 C H bonds being particularly relevant here. 73 Most mechanistic proposals invoke O O bond homolysis to yield a [CuO] + C IIunit that is responsible for attacking the C H bond. 74 Direct evidence for this pathway is scant, however, and differentiating this pathway from one involving direct hydrogen atom abstraction by the [CuOOR] + unit presents experimental challenges (in one study, a case for the latter pathway has been made).…”
Section: (A) Intermediates With Intact O-o Bondmentioning
confidence: 99%
“…Ad rastic enhancement in the reactivity of the cupric superoxide towards phenolic substrates as well as oxidation of substrates possessing moderate C À Hb ond-dissociation energies is observed, correlating with the number and strength of the H-bonding groups.Oxidation and oxygenation reactions are vital for biological and synthetic processes. [1][2][3][4][5][6][7][8][9] In biology,s ome copper-containing metalloenzymes are capable of performing these reactions. [2,10] Forexample,galactose oxidase (GO) is responsible for the oxidation of primary alcohols to aldehydes (Figure 1A); monooxygenases such as peptidylglycine a-hydroxylating monooxygenase (PHM), dopamine b-monooxygenase (DbM), and lytic polysaccharide monooxygenases (LMPOs) catalytically hydroxylate organic substrates containing strong (85-100 kcal mol À1 )C ÀHb ond dissociation energies (BDEs) using dioxygen ( Figure 1B).…”
mentioning
confidence: 99%